Systematic Review: The Effect of Fe Supplementation on Increasing Haemoglobin Levels in Female Adolescent - Negara, Baiq Ramdhani Amelia (Jurnal Biologi Tropis, 2023)
Anemia is related to nutritional problems, where hemoglobin levels in the blood are lower than normal. One age group that is risk to anemia is female adolescent because this age is a growth period that requires higher levels of nutrients, including iron. Prevention and treatment of anemia which is by providing iron supplementation. Giving iron supplementation on female adolescent with the right and effective dose can increase iron level in the body if it consumed regularly. To find out more about the effect of iron supplementation on hemoglobin levels in female adolescent. This study used systematic review and the sources were obtained from the database PubMed, Google Scholar, Cochrane Library, and Research Gate. This systematic review shows a relationship between Fe supplementation and hemoglobin levels. Referring to the results of various studies that have been carried out, it shows that there is a significant effect of Fe supplementation on increasing hemoglobin levels in young women.